The wisdom way of teaching : educating for social conscience and inner awakening in the high school classroom - Schmidt, Martin E. (Transforming education for the future., 2022)
"Immense challenges are now facing the global community as a whole. How can educators train the next generation of students to deal with the vast array of issues that are awaiting them in every field of endeavor and every sector of society? Written as a testimony to 30 years of experimentation with these challenges in mind, Hong Kong International School humanities teacher Marty Schmidt draws upon the ancient Wisdom tradition, as taught by his spiritual teacher Cynthia Bourgeault, to propose curricular frameworks that combine what he calls the yang of social conscience with the yin of inner awakening. This yin-yang approach forms the basis of the Wisdom way of teaching to support the whole-person development of students. Extensive feedback is featured to demonstrate the impact these curricula have upon students as well as the educators who teach these classes. It is hoped that this educational vision that has been successfully implemented at one high-achieving international school in Hong Kong will guide and inspire educators around the world to create their own Wisdom approaches to meet the challenges of the 21st century"--